2020
DOI: 10.1002/advs.202002173
|View full text |Cite
|
Sign up to set email alerts
|

Zeolitic Imidazolate Frameworks as Zn2+ Modulation Layers to Enable Dendrite‐Free Zn Anodes

Abstract: Zinc (Zn) holds great promise as a desirable anode material for next‐generation rechargeable batteries. However, the uncontrollable dendrite growth and low coulombic efficiency of the Zn plating/stripping process severely impede further practical applications of Zn‐based batteries. Here, these roadblocks are removed by using in situ grown zeolitic imidazolate framework‐8 (ZIF‐8) as the ion modulation layer to tune the diffusion behavior of Zn 2+ ions on Zn anodes. The well‐ordered nanoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
165
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(171 citation statements)
references
References 43 publications
5
165
1
Order By: Relevance
“…We have demonstrated that a very simple and easily industrially applicable anode foil polishing process can dramatically improve the lifetime of ZIBs, far exceeding improvements made using complex chemical and physical processes. [14][15][16][17][18][19][20] The electrodes tested showed greatly improved electrochemical plating/ stripping stability, when compared to an as-received Zn foil. Ex situ OM and in situ EC-AFM experiments demonstrated that polished Zn foils with a attened initial surface induced a uniformly plated/stripped Zn structure, lowering the occurrence of dendrites and short-circuit failure in batteries.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have demonstrated that a very simple and easily industrially applicable anode foil polishing process can dramatically improve the lifetime of ZIBs, far exceeding improvements made using complex chemical and physical processes. [14][15][16][17][18][19][20] The electrodes tested showed greatly improved electrochemical plating/ stripping stability, when compared to an as-received Zn foil. Ex situ OM and in situ EC-AFM experiments demonstrated that polished Zn foils with a attened initial surface induced a uniformly plated/stripped Zn structure, lowering the occurrence of dendrites and short-circuit failure in batteries.…”
Section: Discussionmentioning
confidence: 97%
“…10 In particular, it has been reported that the electrolyte composition and the current density at the electrode are major inuencers of dendrite morphology, 11 which can vary from a 1D ramied cone-like topology, to 2D hexagonal platelets and dense 3D structures. 12 Common strategies to achieve uniform Zn deposition include (1) introducing a protection layer on the electrode surface to help homogeneously distribute ions and the electric eld; 13,14 (2) optimizing the material and structure of the Zncontaining electrode, promoting charge transfer; 15,16 (3) modifying the electrolyte, improving interfacial ion migration; [17][18][19] and (4) designing multifunctional separators. 20 Example solutions using these strategies include (1) interfacial protection of the Zn anode by in situ growth of zeolitic imidazolate framework-8 (ZIF-8) layers; 14 (2) design of Zn/carbon nanotube (Zn/CNT) foams 15 or eutectic Zn 88 Al 12 (at%) alloys; 16 (3) electrolyte modifying additives 17,18 or use of high concentration electrolytes; 19 and (4) graphene decorated glass bre separators.…”
Section: Introductionmentioning
confidence: 99%
“…The high energy density, low cost, and the environmentally friendly nature of aqueous zinc-ion batteries (ZIBs) are attractive especially for the large-scale stationary electrical energy storage [1,2]. Unfortunately, ZIBs suffer from the growth of dendrite [3], element dissolution [4], and the formation of irreversible products [5]. In order to solve these issues, great efforts have been devoted to the study on the new Zn-host cathode discovery (manganese-based oxides [6], vanadium-based oxides [7,8], prussian blue analogous [9], and other organic materials [2] etc.…”
Section: Introductionmentioning
confidence: 99%
“…ZIF-8 has attracted significant interest for its easy preparation, ordered nanoporous structure, exceptional mechanical stability and ultrahigh chemical stability resulting from the metal-nitrogen bonds [29]. Notably, it was reported that ZIF-8 could withstand metal ion intercalation/deintercalation [30][31][32], preserving its structure/chemical composition intact during cycles. For example, Fan et al introduced a stable artificial solid electrolyte interphase (SEI) film prepared by polyvinyl alcohol (PVA) cementing a metal-organic framework (Zn-MOF), which is beneficial for inhibiting dendrite growth and easing the volume change [30].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported the commercial LiNi 1/3 Co 1/3 Mn 1/3 O 2 (NCM 333 ) cathode modified by synthesizing ZIF-8 in situ on the surface of NCM 333 , in which ZIF-8 can not only act as a shield against the electrolyte corrosion, but also enable faster lithium-ion transfer at the interfacial regions [ 31 ]. Liu et al proposed an in situ grown porous ZIF-8 as an ideal Zn 2+ modulation layer to effectively regulate the aqueous Zn deposition behavior [ 32 ]. The unique properties make ZIF-8 a promising protective layer for BP.…”
Section: Introductionmentioning
confidence: 99%